EFFECTIVE PEDAGOGICAL METHODS IN DISTANCE EDUCATION: AN ANALYSIS OF MODERN APPROACHES - o‘g‘li, Ismoilov Javohir Alisher (Research Focus International Scientific Journal, 2026)
This article is devoted to analyzing the most effective pedagogical methods used in distance learning environments. It examines how traditional approaches can be adapted to digital settings, explores mechanisms for ensuring interactivity, and discusses ways to enhance learners’ motivation. In particular, the study highlights the effectiveness of combining synchronous and asynchronous learning, as well as the use of microlearning, gamification, and project-based learning methods. The findings suggest that, in achieving success in distance education pedagogical design and the human factor play a more crucial role than technological tools alone.